A Comparative Analysis of the Civil and Public Services in Nigeria (Global Journal of Human-Social Science, 2022)
Public Service and Civil Service have always been used interchangeably to mean one and the same thing. Consequently, some writers and scholars define the Civil Service to include statutory corporations, the military and paramilitary organizations, local government and public corporations established by Act of the National Assembly the teaching service judicial service. This work therefore seeks to establish whether